A stress-associated protein OsSAP8 modulates gibberellic acid biosynthesis by reducing the promotive effect of transcription factor OsbZIP58 on OsKO2. (27th January 2022) - Li, Ming; Zhang, Hui; He, Dongli; Damaris, Rebecca Njeri; Yang, Pingfang
Abstract : Stress-associated protein OsSAP8 negatively regulate GA biosynthesis by binding to the promoter of ent-kaurene oxidase 2 ( OsKO2 ), and reducing the transcriptional activation of OsbZIP58 on OsKO2 via interaction between OsSAP8 and OsbZIP58. Abstract: Gibberellic acid (GA) is a vital phytohormone for plant growth and development. GA biosynthesis is a complex pathway regulated by various transcription factors. Here we report a stress-associated protein 8 (OsSAP8), negatively involved in GA biosynthesis. Overexpression of OsSAP8 in rice resulted in a semi-dwarfism phenotype and reduced endogenous GA3 content. In contrast, an OsSAP8 knockout mutant exhibited higher endogenous GA3 content and slightly increased plant height. Sub-cellular localization analysis of OsSAP8 showed that it could enter the nucleus. Based on electrophoretic mobility shift assay and yeast one hybrid experiments, OsSAP8 was found to bind to the cis -acting regulatory element GADOWNAT of ent -kaurene oxidases (KO2, KO3, KO5). The results from dual-luciferase reporter assays showed that OsSAP8 does not activate LUC reporter gene expression. However, it could interact with basic leucine zipper 58 (OsbZIP58), which has strong transcriptional activation potential on OsKO2 . Moreover, the interaction between OsSAP8, rice lesion simulating disease 1-like 1 (OsLOL1), and OsbZIP58 could reduce the promotive effect of transcription factor OsbZIP58 on OsKO2 . These results provide some new insights on the regulation of GA biosynthesis in rice.